Risk factors and prognosis of poor graft function after allogeneic hematopoietic stem cell transplantation in pediatric: a retrospective study - Pang, Guanxiu; Wang, Xiaobo; Jia, Wenguang; Li, Mengchen; Zhou, Tianyuan; Luo, Jianming; He, Yunyan (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPoor graft function (PGF) represents a serious and potentially life-threatening complication following allogeneic hematopoietic stem cell transplantation (allo-HSCT); however, its etiological risk factors and prognostic implications remain inadequately defined within pediatric populations.MethodsA retrospective cohort study was conducted on 175 pediatric patients undergoing allo-HSCT between 30 June 2018, and 31 December 2022. Patients were stratified into PGF (n = 30) and good graft function (GGF, n = 145) groups. Multivariate logistic regression identified risk factors for PGF, while Cox proportional hazards models evaluated mortality-associated variables. Survival outcomes were analyzed using Kaplan-Meier curves.ResultsKey findings encompass: (1) PGF Risk Factors: Multivariable analysis identified four independent predictors of PGF: age ≥10 years at transplantation (OR = 29.27, 95%CI: 5.70–150.21, P < 0.001), HLA mismatch (OR = 4.11, 95%CI: 1.45–11.65, P = 0.008), cytomegalovirus (CMV) infection (OR = 7.64, 95%CI: 2.31–25.21, P = 0.001), and BK virus (BKV) infection (OR = 12.22, 95%CI: 2.49–59.89, P = 0.002); The model’s predictive performance by ROC analysis yielded an AUC of 0.886 (95%CI: 0.83–0.94; P < 0.001). (2) Survival Analysis: the 4-year overall survival (OS) was profoundly inferior in the PGF cohort compared to the GGF cohort (49.4% ± 10.3% vs. 90.2% ± 2.5%, P < 0.001). (3) Predictors of Mortality: Cox regression identified PGF (HR = 2.39, 95%CI: 1.02–5.59, P = 0.044), acute graft-versus-host disease (grade I/II, HR = 3.43, 95%CI: 1.29–9.15, P = 0.014; grade III/IV, HR = 8.92, 95%CI: 3.19–24.96, P < 0.001), hemorrhagic cystitis (HR = 3.18, 95%CI: 1.37–7.39, P = 0.007), and severe pneumonia (HR = 4.42, 95%CI: 1.92–10.19, P < 0.001) as independent predictors of early mortality.ConclusionAge ≥10 years at transplantation, HLA mismatch, CMV infection, or BK viremia identifies a high-risk cohort of pediatric allo-HSCT recipients who require intensified monitoring for PGF, underscoring an urgent need for effective preventive and therapeutic interventions.